2017
DOI: 10.1021/jacs.7b08861
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of 5-Hydroxymethylfurfural to 2,5-Furandicarboxylic Acid Using O2 and a Photocatalyst of Co-thioporphyrazine Bonded to g-C3N4

Abstract: Selective oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA) is one of the key reactions for producing chemical commodities from biomass and their derivatives. The challenge for this reaction is to develop an efficient catalytic process that can be conducted under mild conditions (room temperature and atmospheric pressure, using oxygen molecules in air as the oxidant) and a recyclable catalyst. Herein we report a photocatalyst of cobalt thioporphyrazine (CoPz) dispersed on g-CN (ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
203
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(219 citation statements)
references
References 42 publications
(70 reference statements)
5
203
0
Order By: Relevance
“…Here the 5,5-dimethyl-l-pyrroline N-oxide (DMPO) can be used to trap the hydroxyl radicals (COH) and superoxide radicals (CO 2 À ), producing the DMPO-COH and DMPO-CO 2 À adducts,r espectively. [32] As shown in Figure 7a,b,n o EPR signal can be observed in the blank experiments, suggesting that the DMPO molecules have no paramagnetic response.F or pure CeO 2 photocatalytic system, the typical peaks of DMPO-COH adducts can obviously observed, whereas the peak intensity of DMPO-CO 2 À adducts is very weak. These results indicate that the CeO 2 photocatalyst is favorable for producing hydroxyl radicals (COH) rather than superoxide radicals (CO 2 À ), which is attributed to its more positive oxidation potential (2.31 V) than the potential of H 2 O/COH (ca.…”
Section: Angewandte Chemiementioning
confidence: 85%
“…Here the 5,5-dimethyl-l-pyrroline N-oxide (DMPO) can be used to trap the hydroxyl radicals (COH) and superoxide radicals (CO 2 À ), producing the DMPO-COH and DMPO-CO 2 À adducts,r espectively. [32] As shown in Figure 7a,b,n o EPR signal can be observed in the blank experiments, suggesting that the DMPO molecules have no paramagnetic response.F or pure CeO 2 photocatalytic system, the typical peaks of DMPO-COH adducts can obviously observed, whereas the peak intensity of DMPO-CO 2 À adducts is very weak. These results indicate that the CeO 2 photocatalyst is favorable for producing hydroxyl radicals (COH) rather than superoxide radicals (CO 2 À ), which is attributed to its more positive oxidation potential (2.31 V) than the potential of H 2 O/COH (ca.…”
Section: Angewandte Chemiementioning
confidence: 85%
“…For example, Xu et al. used cobalt thioporphyrazine (CoPz) dispersed on g‐C 3 N 4 as a catalyst for HMF‐to‐FDCA conversion . The reaction was tested under simulated sunlight using O 2 molecules in air as an oxidant in aqueous solution (pH 9.18).…”
Section: Photobiorefinery Routes For Chemical Productionmentioning
confidence: 99%
“…A series of non‐noble‐metal catalysts were employed for the HMF oxidation . Zhu and co‐workers first prepared a photocatalyst, CoPz/g‐C 3 N 4 , and used Na 2 B 4 O 7 solution, which led to excellent yields of FDCA . Mn–Co bimetallic oxides with different Mn/Co molar ratios were prepared, and nanoscale center‐hollow hexagon MnCo 2 O 4 spinels presented highest activity among all other Mn–Co oxides, with a FDCA yield of 70.9 % .…”
Section: Introductionmentioning
confidence: 99%
“…[5a, 14] Zhu and co-workers first prepared ap hotocatalyst, CoPz/g-C 3 N 4 ,a nd used Na 2 B 4 O 7 solution, which led to excellenty ields of FDCA. [15] Mn-Co bimetallic oxidesw ith different Mn/Com olar ratios were prepared, andn anoscale center-hollow hexagon MnCo 2 O 4 spinels presented highest activity among all other Mn-Co oxides, with aF DCA yield of 70.9 %. [5a] Hayashi et al successfully synthesized MnO 2 with different crystal structures and demonstrated thath igh-surface-area b-MnO 2 presented suitable catalytic activity for the selectiveo xidation of HMF to FDCA.…”
Section: Introductionmentioning
confidence: 99%